2012
DOI: 10.1038/ncb2545
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between BZR1 and PIF4 integrates brassinosteroid and environmental responses

Abstract: Plant growth is coordinately regulated by environmental and hormonal signals. Brassinosteroid (BR) plays essential roles in growth regulation by light and temperature, but the interactions between BR and these environmental signals remain poorly understood at the molecular level. Here, we show that direct interaction between the dark- and heat-activated transcription factor phytochrome-interacting factor4 (PIF4) and the BR-activated transcription factor BZR1 integrates the hormonal and environmental signals. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
859
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(896 citation statements)
references
References 51 publications
31
859
1
5
Order By: Relevance
“…The remaining genes (ZmBZR1, ZmBZR4, ZmBZR5, ZmBZR9, ZmBZR10 and ZmBZR11) were ubiquitously expressed in all the tissues examined, suggesting that they could function as growth regulators during maize development. In fact, recent studies have demonstrated that BR signaling pathway is required to regulate hypocotyl cell expansion (Gallego-Bartolomé et al 2012;Li et al 2012;Oh et al 2012), as well as, to promote the transition from meristematic cells to primordial cells in the shoot (Oh et al 2011;Zhiponova et al 2013). In the root apex, BRs are further involved in controlling root growth, both coordinating root meristem size and also root cell elongation Heyman et al 2013;Vilarrasa-Blasi et al 2014;Vragovic et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining genes (ZmBZR1, ZmBZR4, ZmBZR5, ZmBZR9, ZmBZR10 and ZmBZR11) were ubiquitously expressed in all the tissues examined, suggesting that they could function as growth regulators during maize development. In fact, recent studies have demonstrated that BR signaling pathway is required to regulate hypocotyl cell expansion (Gallego-Bartolomé et al 2012;Li et al 2012;Oh et al 2012), as well as, to promote the transition from meristematic cells to primordial cells in the shoot (Oh et al 2011;Zhiponova et al 2013). In the root apex, BRs are further involved in controlling root growth, both coordinating root meristem size and also root cell elongation Heyman et al 2013;Vilarrasa-Blasi et al 2014;Vragovic et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The key roles of GA and light signalling in attenuating the ABA responses during early seedling development have long been known 4 , and recent studies have revealed the essential functions of BR signalling pathways in the regulation of GA-and light-mediated plant development 1,3 . Exogenous BR application rescued the low germination phenotype of GA-related mutants and BR-defective mutants are hypersensitive to ABA during early seedling development and stomatal closure [14][15][16] .…”
mentioning
confidence: 99%
“…Owing to high vulnerability to a vast array of stresses in early seedling developmental processes, multiple environmental and intrinsic signalling factors are intricately integrated to finely control these developmental processes. The signalling networks that integrate brassinosteroids (BRs), gibberellin (GA), abscisic acid (ABA) and light signals are important factors in the regulation of seed development, dormancy, germination and post-germinative developmental processes [1][2][3][4] . ABA plays important regulatory roles in maintaining seed dormancy and early seedling developmental arrest checkpoints 5 .…”
mentioning
confidence: 99%
“…In the presence of BR, BZR1 and BES1 are dephosphorylated and activated for regulation of BR-inducible gene expression, including many genes related to cell elongation, such as PACLOBUTRAZOL RESISTANCEs (PREs), XYLOGLUCAN ENDOTRANSGLYCOSYLASE/HYDROLASEs (XTHs) and EXPANSINs (EXPs). 10,12,14,15 Sugars repress plant growth in the light, whereas they promote growth in the dark, indicating that the sugar regulation of growth is mediated through different pathways in the light and dark. 4,[15][16][17][18][19] In Arabidopsis, Phytochrome-Interacting Factors (PIFs) and the plant hormone gibberellin (GA) have been shown to play important roles in sugar-induced hypocotyl elongation under both dark and short photoperiod conditions.…”
mentioning
confidence: 99%
“…9,10 In particular, BRs stimulate cell elongation by increasing cell wall plasticity and affect cell expansion via regulation of microtubule dynamics. [10][11][12] The BR receptor BRASSI-NOSTEROID INSENSITIVE1 (BRI1) heterodimerizes with BRI1 ASSOCIATED KINASE1 (BAK1), the BRI1 co-receptor, after binding to BR. BRI1 and BAK1 subsequently act together to inhibit the GSK3-like kinase BRASSINOSTEROID INSEN-SITIVE2 (BIN2), a negative regulator of BR signaling.…”
mentioning
confidence: 99%